Design and Analysis of a Novel Sidewalk Following Visual Controller for an Autonomous Wheelchair - UGUR, E.; KARA, T.; ABDULHAFEZ, A.; OSMAN, I. H. (Advances in Electrical and Computer Engineering, 2024)
This paper presents a study that focuses on sidewalk following problem of an autonomous wheelchair. The main goal is to propose a solution to the urban mobility problem of people with walking disabilities. The study offers an efficient control system design for this task. A linearized wheelchair model is constructed and image-based visual servoing is introduced to evaluate the performance of tracking yellow tactile pavement on sidewalk with optimal control. Reference trajectory sets are created using robust vanishing point for sidewalk following by employing the Hough Lines method. These reference paths are tested with two control methods of Linear Quadratic Regulator (LQR) control and Pole Placement (PP) control. Both control methods are applied through simulation on the autonomous wheelchair model, and efficacy of sidewalk following under these control methods is discussed comparatively. Disturbance attenuation results of the given optimal control methods and simulation outputs prove the efficacy of the model and the designed control systems. LQR control method proves to have better performance in system response in comparison to PP control method.